Air hygienic condition in a room served by a ventilation system, in which birds were nested - a case study - Szczęśniak, Sylwia; Trusz, Agnieszka (Instal, 2021)
The article presents the results of microbiological tests carried out in the exhaust duct where the birds were nesting, in the air handling unit and in the room it serves. The research was carried out in order to determine the hygienic condition of the air in the room served by the ventilation system in which the birds nested. The effectiveness of a portable device for disinfecting air in rooms, which uses UV-C radiation of overstandard power 330 W, was also tested.